Analisa Pengaturan Kecepatan Terhadap Perubahan Frekuensi Pada Motor Induksi Tiga Fasa Berbasis VSD: Analysis Control Speed Of Frequency Changes In Three Phase Induction Motor Based On VSD - Bagas Nur Ramadhan (Institut Riset dan Publikasi Indonesia, 2022)
The development of science and technology at this time continues to grow rapidly both in the industrial sector and in households. In the industrial field, three-phase induction motors are widely used as drives to assist the production process. Setting the speed of a three-phase induction motor can be done by adjusting the frequency that goes into the three-phase motor. Setting the magnitude of the frequency using a Variable Speed ??Drive (VSD). In addition to simplifying frequency regulation using a VSD so that there is no need to visit the location where the three-phase induction motor is located, the Internet of Things (IoT) is used to be able to adjust the frequency scale remotely.